Peran Pemberian Tunjangan Dalam Mengembangkan Sumber Daya Manusia Berdasarkan Perspektif Bisnis Islam (Studi Pada PT Great Giant Foods Lampung Tengah) - Fatih Fuadi; Depi Melsandi (Jurnal Ekonomi dan Bisnis Digital, 2023)
Human Resources is one of the elements that really determines the success of an organization. This situation makes human resources an asset whose efficiency and productivity must be increased. PT Great Giant Foods is a company with vertically integrated agricultural and manufacturing business lines in growing, producing, shipping fresh fruit and processed juices, meat and milk. One of the efforts that PT Great Giant Foods can take to create these conditions is by providing benefits to employees. Providing allowances can increase employee performance productivity, of course employee performance plays an important role for the company to achieve the company or organization's goals. The research method used is qualitative with data collection carried out namely observation, interviews and documentation. The selection of sources was carried out by researchers using purposive sampling, that is, researchers chose based on criteria who would be used as research sources, namely the head of human resources, permanent employees and non-contract employees at PT Great Giant Foods Bandar Lampung. The research results show that regarding the provision of allowances by PT. Great Giant Foods Central Lampung to its employees is in accordance with applicable laws and regulations, where the higher the employee's skills and knowledge, the higher the level of payment. Meanwhile, based on an Islamic business perspective, the allowance system implemented is in accordance with Islamic-based management, namely based on expertise and situations fairly. However, allowances are given based on the type of work provided and type of workforce because the allowances given to permanent employees are different from the allowances given to non-contract employees.